Macroalgae diversity in the Pari Island Cluster, Seribu Islands District, Jakarta, Indonesia - SRI HANDAYANI; IMAM WIDHIONO; DWI SUNU WIDYARTINI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Handayani S, Widhiono I, Widyartini DS. 2023. Macroalgae diversity in the Pari Island Cluster, Seribu Islands District, Jakarta, Indonesia. Biodiversitas 24: 1659-1667. Macroalgae are primary producers of the ocean that support the life of other organisms at higher trophic levels in aquatic ecosystems. This study aimed to determine the diversity of macroalgae in the Pari Island cluster and the diversity of water quality. The research method used is the survey method, with the quadratic transect method. Ecological index analysis using PAST 4.0 software. The relationship between diversity correlation and water quality using PCA software. The results of the study found 22 species of macroalgae consisting of 3 divisions, namely Chlorophyta (11 species), Phaeophyta (4 species), and Rhodophyta (7 species). Diversity of Pari Island (H'=2.314, E=0.594, D=0.121) and Kongsi Island (H'=1.191, E=0.481, D=0.211). The largest species are Acanthophora spicifera (M.Vahl) Børgesen (Rhodophyta), with 396 individuals; Caulerpa racemosa (Forssk.) J.Agardh (Chlorophyta), with 343 individuals; and Padina australis Hauck (Phaeophyta), with an individual number of 130. Macroalgae diversity in the Pari Island Cluster belongs to the moderate category. The diversity of macroalgae in the Pari Island Cluster is influenced by physical factors of temperature, salinity, brightness, depth, and current speed, as well as chemical factors of nitrate, orthophosphate, dissolved oxygen, heavy metal levels of Pb, Cu, and pH.